2000
DOI: 10.1017/s0022377800008448
|View full text |Cite
|
Sign up to set email alerts
|

Spatial absorption of a magnetosonic wave in a dusty magnetized plasma

Abstract: Abstract. The dielectric tensor for a multicomponent magnetized dusty plasma, including the effect of capture of plasma electrons and ions by the dust particles, is rewritten in order to provide expressions more suitable for applications. We use this tensor to study the spatial absorption of a magnetosonic wave, including effects up to second order in the Larmor radius. We analyse the absorption of the wave due to the presence of dust particles with variable charge and the modification of this absorption due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…The study expands previous analyses in which the case of Langmuir waves and isotropic Maxwellian distributions has been considered [9]. To our knowledge, this is one of the first instances of numerical analysis including the effect of the 'new' contribution, which usually only appears in formal analysis of wave propagation in dusty plasmas [4,15,16,[19][20][21]. For this investigation we have considered parameters which are in the range of parameters typical of stellar winds, and the results obtained have shown that the contribution of the 'new' components is very small compared to the 'conventional' contribution.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The study expands previous analyses in which the case of Langmuir waves and isotropic Maxwellian distributions has been considered [9]. To our knowledge, this is one of the first instances of numerical analysis including the effect of the 'new' contribution, which usually only appears in formal analysis of wave propagation in dusty plasmas [4,15,16,[19][20][21]. For this investigation we have considered parameters which are in the range of parameters typical of stellar winds, and the results obtained have shown that the contribution of the 'new' components is very small compared to the 'conventional' contribution.…”
Section: Discussionsupporting
confidence: 53%
“…Using this basic framework, we arrive to expressions for the components of the dielectric tensor which can be separated into two kinds of contributions [15,16] …”
Section: The Homogeneous Magnetized Dusty Plasma Model and The Componmentioning
confidence: 99%
See 1 more Smart Citation
“…The formulation has been applied to the particular case of low-frequency waves propagating along the ambient magnetic field, incorporating many details which have appeared in previous publications. 32,33 The results which we have obtained show that, as in the case of dustless plasmas, the dispersion relation describes two different modes, identified for higher frequencies as the whistler waves and as the circularly polarized waves. In the absence of dust these two modes collapse together, for frequencies well below ion cyclotron frequency, forming the well-known branch of the Alfvén waves.…”
Section: Introductionmentioning
confidence: 60%
“…Hðp z Þd 1;Àn z FðpÞ; (9) wheren K Áx ¼ n x andn K Áẑ ¼ n z , withn K being an unitary vector pointing in the direction of propagation of the radiation, and where bð Þ; Kð Þ and r j P are quantities mentioned in Sec. II, which have a more detailed specification in Appendix.…”
Section: General Features Of the Modelmentioning
confidence: 99%